(untitled) (Revista de Artes Marciales Asiáticas, 2015)
The purpose of this study was to investigate the role of taekwondo (TKD) training on the subjective well-being (SWB) of adolescents (12-18 years old) in Addis Ababa city. A cross-sectional survey method was used; self-administered questionnaire was the main data collection tool. A total number of 162 adolescents (108 TKD adolescents from four randomly selected TKD clubs and 54 non-TKD adolescents from a randomly selected public high school), participated in the study. The study sought to determine TKD adolescents’ level of SWB as measured by the Personal Wellbeing Index – School Children (PWI-SC). Besides, adolescents in different groups (TKD adolescents in three groups according to rank/belt level and TKD adolescents and non-TKD adolescents) were compared based on their score of PWI-SC. Results of the study showed that: (1) TKD adolescents had high level (mean points) of SWB as measured by the PWI-SC, i.e., 81.95 (95%CI: 79.70 to 84.20); (2) there was no significant difference in SWB among the three groups of TKD adolescents (lower, middle and high level belts) (F(2, 81) = 1.58, p > .05.); and (3) when compared with non-TKD adolescents, TKD adolescents were found to have a significantly higher mean points of SWB, (t = 4.25(77.97), p < 0.001; d = 0.79). Overall, the results of this study indicated the training of TKD can have a positive contribution to adolescents’ well-being.